Sediment control interventions and river flow dynamics: impact on sediment entry into the large canals - Ashraf, M.; Bhatti, Muhammad Tousif; Shakir, A.S.; Tahir, A.A.; Ahmad.A. (Springer, 2015)
At Marala barrage, two canals, i.e. Marala Ravi Link Canal (MRLC) and Upper Chenab Canal (UCC) off-take from left side of the River Chenab. MRLC has a very old history of experiencing sedimentation issues. Several attempts have been made to counterfoil or minimize this problem in the recent past. Two remarkable measures are the remodeling of MRLC in 2000-2001 (in-tervention-1) and the shifting of the confluence point of a heavily sediment-laden upstream tributary of the Chenab River by construction of a spur dike in 2004 (intervention-2). This paper investigates the effectiveness of these structural interventions as sedimentation control measures. The baseline period is selected from 1997 to 2000 and the impact is analyzed for two post-intervention time steps, i.e. evaluation period-1 ranging from 2001 to 2004 and evaluation period-2 from 2005 to 2011. Results obtained from double mass analysis revealed that sediment load increased by 33 and 8 % due to intervention-1, while decreased by 12 and 22 % due to intervention-2 in MRLC and UCC, respectively. The results suggest that monsoon floods are mainly responsible for sediment loading in the canals (66 % for UCC and 73 % for MRLC), supported by the finding that effective discharge (1900 m3 s-1) is almost twice the mean annual river discharge. The discharge classes between 900 and 2900 m3 s- 1 are mainly responsible for major proportion (89 % in MRLC and 86 % in UCC) of the total sediment load over the 15-year study period. The intervention-1 could not minimize the sediment entry into the canals; rather it aggravated the situation. The intervention-2, however, proved a useful structural measure in this regard.